Implementation of Ankle Pump Exercise for Edema Reduction in Chronic Kidney Disease Patients - Septiana, Nita Tri; Sangadah, Diyah Kamilatus; Nurhayati; Nurahman, Novema Ashar (Jurnal Pinang Masak, 2025)
Chronic Kidney Disease (CKD) is a global public health problem characterized by a gradual loss of kidney function over time. Edema is a common clinical manifestation in patients with Chronic Kidney Disease (CKD), particularly in the advanced stages, resulting from impaired fluid and sodium regulation due to declining kidney function, often accompanied by hypoalbuminemia and increased capillary hydrostatic pressure. The objectives of this study was to describe the the implementation of ankle pump exercise to reduce the degree of edema in patients with CKD. The study used a descriptive case study method based on Evidence-Based Nursing Practice (EBNP), using a nursing care process approach consisting of assessment, nursing diagnosis, intervention, implementation, and evaluation. The subjects in this study were 3 respondents who are case-managed patients within the nursing care approach. The ankle pump exercise was implemented over 3 days, with a total of 6 sessions conducted twice a day, each lasting 8 minutes per session. The results of the analysis before and after therapy with ankle pump exercises showed that ankle pump exercises have an effect on the degree of edema in the lower extremities of patients  with CKD. Ankle pump exercise therapy has been proven to help reduce the degree of edema in CKD patients. This intervention is highly relevant to nursing practice because it is simple, can be performed independently by patients, and contributes to an improved quality of life.